1985
DOI: 10.1002/jez.1402360309
|View full text |Cite
|
Sign up to set email alerts
|

Pattern‐deficient forelimb regeneration in adult bullfrogs

Abstract: This study was designed to test the ability of adult bullfrogs (Rana catesbeiana) to regenerate forelimbs, both with and without various experimental treatments. Distal humerus-level forelimb amputations provided with additional deviated (sciatic) nerve and/or repeated soft-tissue injury exhibited considerable outgrowth. However, control sham-operated forelimbs also produced regenerates with comparable frequency, size, and morphological complexity. The lengths of the regenerates ranged from 0.4 to 2.6 cm, repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…5 anterior (19). This is consistent with an earlier notion that the breaking of symmetrical assembly of a photoreceptor cluster into asymmetry occurs as R4 loses its contact with R8 resulting in the breaking of R3-R4 symmetry (26). It was also suggested that the sple function is required in R3, R4, or R5 for correct polarity of a photoreceptor cluster (19).…”
Section: Resultssupporting
confidence: 91%
“…5 anterior (19). This is consistent with an earlier notion that the breaking of symmetrical assembly of a photoreceptor cluster into asymmetry occurs as R4 loses its contact with R8 resulting in the breaking of R3-R4 symmetry (26). It was also suggested that the sple function is required in R3, R4, or R5 for correct polarity of a photoreceptor cluster (19).…”
Section: Resultssupporting
confidence: 91%
“…Wings were dissected and mounted in 50% ethanol, 50% lactic acid. Sections of adult eyes were prepared as described in (Tomlinson, 1985).…”
Section: Histochemical and Microscopic Analysismentioning
confidence: 99%
“…Tissue regeneration occurs in many different animal species, with the capacity for regeneration varying significantly among even highly related animals (Alibardi, 2017; Brockes & Gates, 2014; Dwaraka & Voss, 2021; Goss & Holt, 1992; McLaughlin et al, 1983; Nogueira et al, 2016; Simon & Tanaka, 2013; Tomlinson et al, 1985). Not only do these different vertebrate species share an ability to regenerate but there is an overlap in the molecular pathways involved in regeneration between the early blastema of ray‐finned fish and lobe‐finned vertebrates (Darnet et al, 2019).…”
Section: Introductionmentioning
confidence: 99%